Can we just play? Internal validity of assessing physiological state with a semistandardized kicking drill in professional Australian football - Arguedas-Soley, A.; Shushan, T.; Murphy, A.; Poulos, N.; Lovell, R.; Norris, D. (International Journal of Sports Physiology and Performance, 2024)
Purpose To examine associations between exercise heart rate (HRex) during a continuous-fixed submaximal fitness test (CF-SMFT) and an intermittent-variable protocol (semistandardized kicking drill [SSD]) in Australian Football athletes, controlling for external intensities, within-session scheduling, and environmental conditions.